Managing sexual receptivity and ovulation induction in rabbit does: evidence from recent research - Pilar G. Rebollar; María Arias-Álvarez; Pedro L. Lorenzo; Rosa M. García-García (World Rabbit Science, 2023)
The sexual receptivity and ovulation induction of the reproductive rabbit are key points determining their success in productive life. Adequate synchronisation of the sexual receptivity methods of inseminated rabbit does unquestionably favours fertility and prolificacy outcomes. This review aims to bring together the different methods applied in synchronising primiparous rabbits and the consequences at metabolic, endocrine and ovarian levels, as well as in the embryonic, foetal and post-natal development that our research group has studied over the years. Likewise, the latest advances regarding ovulation induction in the rabbit are described, as well as the search for alternatives to the intramuscular injection of synthetic analogues of gonadotropins and seminal plasma components that could be involved in this process. Different experiments performed with a physiological basis confirm that nerve stimulation during artificial insemination or coitus is especially important in the ovulation induction reflex in rabbit females.